Determinación del contenido de compuestos fenólicos y actividad antioxidante de extractos de la raíz de Smilax cumanensis - Armas Maytahuari, Joao Junior (2024)
Objective: To determine the antioxidant activity and the content of phenolic compounds in S. cumanensis root extracts. Methodology: The plant species was collected in the Zungarococha settlement, San Juan Bautista district. Antioxidant activity was assessed using the DPPH free radical scavenging assay, while phenolic compounds were quantified by UV-visible spectrophotometry. Results: A notable concentration of phenolic compounds was revealed in the extracts, including total phenols (16,881.61 mg/100g), flavonoids (12.49 mg/100g), anthocyanins (6.31 mg/100g), and catechins (0.003 mg/100g). Regarding antioxidant activity, the dried S. cumanensis (zarzaparrilla) sample showed an IC50 of 46.33 mg/mL, compared to an IC50 of 83.80 mg/mL for the liquid sample. Conclusion: The dried S. cumanensis sample demonstrated greater antioxidant activity compared to the liquid sample, both in terms of IC50 and antioxidant capacity. These results indicate that the dried sample is more effective in neutralizing free radicals and providing antioxidant benefits.